2020
DOI: 10.5723/kjcs.2020.41.2.27
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Adverse Childhood Experiences and the Risk of Lifetime Suicide Attempts

Abstract: Objectives: This study aims to examine the effect of adverse childhood experiences (hereafter ACE) on the risk of lifetime suicide attempts. Methods: Cross-sectional data of a sample of 1,396 individuals aged 18-64 years were obtained from the Korean General Social Survey (KGSS) in 2012. Frequency, chi-square analysis, and logistic regression were conducted, utilizing both the SPSS 25.0 and Stata 16. Additionally, population attributable fractions (hereafter PAF) were calculated to determine the proportion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…(pooled) (Table 3) , ACE (Chartier et al, 2010;Font & Maguire-Jack, 2016;Merrick et al, 2017) ACE (Danese et al, 2009;Downey et al, 2017;Font & Maguire-Jack, 2016;Gilbert et al, 2015;Y. H. Kim, 2017;J. Kim & Son, 2020;M.…”
Section: 연구대상자의 일반적 인구사회학적 특성 및 Ace 유무에 따른 차이mentioning
confidence: 99%
“…(pooled) (Table 3) , ACE (Chartier et al, 2010;Font & Maguire-Jack, 2016;Merrick et al, 2017) ACE (Danese et al, 2009;Downey et al, 2017;Font & Maguire-Jack, 2016;Gilbert et al, 2015;Y. H. Kim, 2017;J. Kim & Son, 2020;M.…”
Section: 연구대상자의 일반적 인구사회학적 특성 및 Ace 유무에 따른 차이mentioning
confidence: 99%
“…Compared with the group with a cumulative ACE score of zero, the group with a score of four or higher was four times more likely to have suicidal thoughts in adulthood (Park, 2021). In another study, those who experienced four or more ACEs were more than five times more likely to attempt suicide in adulthood than those who did not (Kim & Son, 2020). These results provide strong evidence that ACEs should be considered as one of the crucial factors in the study of suicide prevention in South Korea.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 In addition to primary mental illness, psychological trauma such as bullying, sexual assault, intimate partner violence and childhood adverse events appear to have a significant association with suicidal ideation. 17,18,19,20 Previous studies have shown that a poor level of financial support, unemployment of parents and family instability are risk factors for suicidal ideation amongst students. 21,22 Because of the dearth of published studies on suicidal ideation amongst students at institutions of higher learning in South Africa, it is unclear what the prevalence and risk factors for suicidal ideation are amongst such students in the country.…”
Section: Introductionmentioning
confidence: 99%